2013
DOI: 10.2174/1874210601307010152
|View full text |Cite
|
Sign up to set email alerts
|

A Keratocyst in the Buccal Mucosa with the Features of Keratocystic Odontogenic Tumor

Abstract: A 74-year-old male patient consulted us for an elastic firm mass in the right buccal mucosa. CT examination revealed a well-circumscribed oval cystic lesion in the anterior region of the masseter muscle. On MRI, the lesion showed a low signal on T1-weighted image and a high signal on T2-weighted image. Aspiration biopsy demonstrated the presence of squamous cells in whitish liquid. Under the diagnosis of epidermoid cyst, the lesion was intraorally extirpated under general anesthesia. The lesion was cystic at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The stimulus for cystic change and increased proliferative activity was not evident, but it has been suggested that chronic mild inflammation may be a contributing factor for epithelial proliferation in benign conditions. Interestingly, despite the well‐established tendency of OKC to recur, neither this nor the other five cases of ‘mucosal’ keratocyst have done so at the time of publication, despite several years of follow‐up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The stimulus for cystic change and increased proliferative activity was not evident, but it has been suggested that chronic mild inflammation may be a contributing factor for epithelial proliferation in benign conditions. Interestingly, despite the well‐established tendency of OKC to recur, neither this nor the other five cases of ‘mucosal’ keratocyst have done so at the time of publication, despite several years of follow‐up.…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, ‘peripheral’ OKC affecting the gingiva are much rarer, though they have been reported in the literature for more than 25 years. Since 2008, five keratocysts have been described which occurred in the submucosal tissues of the cheek, specifically in the buccal space. The origin of this even rarer extragnathic variant of soft tissue, or ‘mucosal keratocyst’, has been assumed to be remnants of dental lamina, the local salivary glands or skin appendages.…”
Section: Introductionmentioning
confidence: 99%
“…1 Keratocystic odontogenic tumor (KCOT), solitary or multiple, develops in the mandible or maxilla, and occasionally on the gingiva as a peripheral counterpart. 2 Multiple KCOT is usually one of the stigmata of the inherited nevoid basal cell carcinoma syndrome (NBCCS). KCOT may evince a syndromic association (henceforth sKCOT) or non-syndromic incidence (henceforth OKC).…”
Section: Introductionmentioning
confidence: 99%
“…This kind of KCOT mainly appears in young females (average age 18) [ 9 ]. Shetty et al described a case of KCOT with mural calcification [ 4 ], whereas Patil et al – the occurrence of “spider-like bodies” in KCOT’s inflammatory cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%